The Influence of Spiritual Support Based on Visual Audio on Stress and Sleep Quality of Pre-TKR (Total Knee Replacement) Patients - Eva Vera Zulkarnain; Eppy Setiyowati; Abdul Muhith; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2026)
Total Knee Replacement (TKR) is a treatment for end-stage knee OA (Osteoarthritis) that does not show improvement after non-operative treatment. The psychological impact on patients who will undergo TKR surgery is stress and sleep quality disturbances. Spiritual Support Based On Visual Audio is a form of distraction for pre-TKR surgery patients to adapt to stress and sleep disturbances. The purpose of this study was to analyze the effect of Spiritual Support Based On Visual Audio on stress and sleep quality in pre-TKR surgery patients. The method used was a quasi-experimental with a pretest-posttest with a control group design. A population of 20 patients used total sampling. The research instrument used a module, audio visuals containing prayers and hymns, the DASS (Depression Anxiety Stress Scale) Questionnaire with a validity of 0.862 and a reliability of a special stress questionnaire = 0.954 and the RCSQ (Richards Champbell Sleep Questionnaire) obtained a validity of 0.822 and a reliability of 0.891. Data analysis used the Wilcoxon Rank Test. The results of the study obtained a p value <0.05, meaning that there is an effect of Spiritual Support Based on Visual Audio on stress and sleep quality in pre-TKR patients. The conclusion is that there is an effect of Spiritual Support Based on Visual Audio on stress and sleep quality in pre-TKR patients at Gotong Royong Hospital Surabaya.